Assessing the optical properties of chalcogenide glasses and fibres: towards the development of new light sources - Fang, Yuanrong (2019)
Owing to their properties of mid-infrared (MIR) transparency, high refractive index, low phonon energy, high optical non-linearity, and an ability to dope them with rare-earth element ions, chalcogenide glasses are a promising candidate for planar photonic integrated circuits, and narrow- and broad-band fibre-based laser sources and amplifiers for the MIR. Although much research effort has been paid to the development and characterisation of chalcogenide glasses for photonics, relatively little refractive index dispersion data are presently available at MIR wavelengths. Therefore, the aim of this Project is to assess the optical properties, especially refractive index, material dispersion and thermo-optic coefficient, of the chalcogenide glasses and fibres (As40Se60, Ge16As24Se15.5Te44.5, Ge20Sb10Se70 and Ge20Sb10Se67S3 at. % (atomic %)) fabricated for developing MIR light source and fibre-sensing. As a well-know technique to determine the refractive index with a high accuracy, the minimum deviation method is applied to determine the refractive index of the chalcogenide glasses investigated in this Project. The errors in each part of the minimum deviation measurement using our experimental setup are analysed using a commercial LAF850322 right-angled prism. The refractive indices of different chalcogenide glass prisms are then successfully measured at wavelengths of ~1500 nm, 3100 nm, 3800 nm and 6450 nm with a standard deviation of less than 0.001 refractive index unit (RIU)) using different light sources. The results obtained are taken as the benchmark values for the techniques developed later. After analysing in the literature the refractive index change with changing composition of Ge-As-Se-Te, an interpolation modelling scheme for estimating the refractive index of GexAsz-xSe100-z-yTey within the range of 10≤x≤25, 40≤y≤50 and 30≤z≤40 is set up with an error of less than 0.22 %. To investigate a suitable refractive index model to describe the refractive index dispersion of chalcogenide glasses in the MIR region, several refractive index models (the Cauchy and Sellmeier models) are applied to fit the refractive index data points of the Ge16As24Se15.5Te44.5 at. %, As40Se60 at. %, Ge10As23.4Se66.6 at. %, Ge16.5As16Ga3Se64.5 at. % and Pr3+ doped Ge16As21Ga1Se62 at. % glasses made in-house, obtained using spectroscopic ellipsometry at MIR wavelengths. A two-term Sellmeier model, with one resonant optical bandgap electronic absorption and one resonant MIR fundamental vibrational absorption, is verified to be unique and sufficient to describe the refractive index dispersion of the chalcogenide glasses within their transparent windows. The numerical aperture of a step-index fibre based on an As40Se60 at. % core and Ge10As23.4Se66.6 at. % cladding and a step-index fibre based on the Ge16As24Se15.5Te44.5 at. % and Ge10As23.4Se66.6 at. % glass pair is respectively calculated to be larger than 0.97 and 1.86 over the wavelength range from 0.5 to 30 µm. The two-term Sellmeier fits to the measured refractive index data are also used to calculate material dispersion characteristics for these compositions. The well-known method presented by Swanepoel can be used to determine the refractive index dispersion of thin films over the wavelength range from 0.7 to 2 µm from wavelength values at maxima and minima, only, of the transmission interference fringes. In order to extend this method into the MIR spectral region (measurements described are over the wavelength range from 2 to 25 µm), the method is improved by using a two-term Sellmeier model instead of the Cauchy model as the dispersive equation. The refractive index dispersion of hot-pressed chalcogenide thin films is determined by the improved method with a standard deviation of less than 0.002. The accuracy of the method is shown to be within 0.4% with of a benchmark refractive index value obtained from prism measurements at a wavelength of 3.1 µm. The refractive indices of other compositions investigated in this Project were also determined using this method. A simple technique is proposed to determine the small refractive index contrast of a low numerical aperture (NA) glass pair. A core fibre (Ge20Sb10Se70 at. %) is hot-pressed together with a cladding fibre (Ge20Sb10Se67S3 at. %) to form a two-composition thin film with the advantages of the two glasses having the same thermal history and post-fibre processing. The refractive index contrast can be simply determined with an error of less than ±0.002 only using their FTIR (Fourier transform infrared) transmission spectra. Moreover, a 3 at. % substitution of S for Se in the Ge-Sb-Se glass system is shown to blue-shift the visible (VIS) optical bandgap, the MIR fundamental vibrational absorption bands, the zero dispersion wavelength and lower the refractive index. In this Project, the effect of temperature on the optical properties of chalcogenide glasses, including their transparent windows, impurity and multiphonon absorptions, refractive index, zero dispersion wavelengths and thermo-optic coefficients of the chalcogenide glasses is investigated. In order to obtain the continuous thermo-optic coefficient of a chalcogenide glass at MIR wavelengths, the FTIR continuous dn/dT method is proposed based on the FTIR transmission spectra at upper and lower temperatures. It is shown that this method can successfully determine the thermo-optic coefficients of the chalcogenide glass thin films (Ge16As24Se15.5Te44.5 at. % and As40Se60 at. %) over the wavelength range from 2 to 20 µm with an error of less than ±7.5 ppm (parts per million) /ºC. The proposed method is shown to provide a much lower error than the minimum deviation method and the improved Swanepoel method. In summary, some techniques are successfully developed to obtain the refractive index, material dispersion data and thermo-optic coefficients for bulk chalcogenide glasses and chalcogenide glass thin films in the MIR region in this Project. These data are useful for the design of step-index fibres for new MIR light sources and fibre-sensing.